Thematic Analysis of Research Mediums’ Experiences of Discarnate Communication - ROCK, ADAM J.; BEISCHEL, JULIE; SCHWARTZ, GARY E. (Journal of Scientific Exploration, 2010)
Mediums claim to be able to report accurate and specific information about the deceased loved ones (termed discarnates) of living people (termed sitters) even without any prior knowledge about the sitters or the discarnates and in the complete absence of any sensory feedback. Despite recent experimental research investigating this phenomenon (e.g., Beischel & Schwartz, 2007a), no systematic qualitative studies have been conducted. Consequently, eight research mediums were asked to describe in as much detail as possible how they personally experience receiving communication from a discarnate, as part of a comprehensive nine-step subject screening procedure. Thematic analysis revealed seven comprehensive constituent themes that were used to formulate a fundamental structural definition. Keywords: research mediums—discarnate communication—phenomenology— thematic analysis